PERANCANGAN ELECTRONIC CUSTOMER RELATIONSHIP MANAGEMENT (E-CRM) PADA PT WAHANAARTHA RITELINDO - Adytia Fantori; Evi Yulianingsih (Simtek : jurnal sistem informasi dan teknik komputer, 2026)
This study aims to design and implement a sales information system at PT Wahanaartha Ritelindo, which currently still uses a non-integrated method for sales reporting, service management, and promotional distribution analysis for customers. The lack of integration in the current system has led to several issues, such as inaccuracies in promotional distribution, delays in report delivery, and limited interaction with customers after motorcycle sales and services. To address these problems, this study employs the Electronic Customer Relationship Management (E-CRM) development method, which allows for rapid iteration and direct user evaluation throughout the system development process. The result of this research is an E-CRM system capable of recording, managing, and presenting motorcycle sales data and customer information in real-time. This system enhances efficiency and accuracy in sales processes and provides easier access for management to conduct market analysis and develop marketing strategies. The implementation of this system is expected to support increased motorcycle sales, strengthen long-term customer relationships, and improve customer loyalty and trust in PT Wahanaartha Ritelindo.